2008
DOI: 10.1530/rep-07-0419
|View full text |Cite
|
Sign up to set email alerts
|

Propagation of bovine spermatogonial stem cells in vitro

Abstract: The access to sufficient numbers of spermatogonial stem cells (SSCs) is a prerequisite for the study of their regulation and further biomanipulation. A specialized medium and several growth factors were tested to study the in vitro behavior of bovine type A spermatogonia, a cell population that includes the SSCs and can be specifically stained for the lectin Dolichos biflorus agglutinin. During short-term culture (2 weeks), colonies appeared, the morphology of which varied with the specific growth factor(s) ad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

15
113
2
1

Year Published

2009
2009
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 139 publications
(131 citation statements)
references
References 41 publications
15
113
2
1
Order By: Relevance
“…To reduce the interference of somatic cells, the subculturing MGSCs are maintained in media supplemented with growth factors. Glial cell linederived neurotrophic factor (GDNF) has far been demonstrated to play vital roles in SSC self-renewal and long-term cultures of SSCs across species [2,9,16,17,19,21,[25][26][27]32]. However, we observed that GDNF showed little positive effects on porcine MGSC colony formation (data not shown), which is in line with the previous report by Kuijk et al [20].…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…To reduce the interference of somatic cells, the subculturing MGSCs are maintained in media supplemented with growth factors. Glial cell linederived neurotrophic factor (GDNF) has far been demonstrated to play vital roles in SSC self-renewal and long-term cultures of SSCs across species [2,9,16,17,19,21,[25][26][27]32]. However, we observed that GDNF showed little positive effects on porcine MGSC colony formation (data not shown), which is in line with the previous report by Kuijk et al [20].…”
Section: Discussionsupporting
confidence: 91%
“…bFGF, as well as EGF, has far been used to stimulate in vitro proliferation of MGSCs from mice, rats, pigs and bulls [2,15,19,20,25]. In our study, despite the addition of bFGF at 1, 5 ng/ml significantly promoted the formation of large colonies, a devastating effect of bFGF at 10 ng/ml was observed.…”
Section: Discussionmentioning
confidence: 46%
“…Among the livestock species, goats are often considered as unique for transgenesis because of their small body size, shorter gestation period, prolificacy and relatively higher protein content in their milk [29]. There are several reports of SSC culture in different species including mice [22,30], rat [31,32], cattle [11,33], buffalo [34,35] and human [13,36]. But the isolation and enrichment as well as establishment of long term culture system for SSCs have not yet been exploited substantially in goats except a very recent report [10].…”
Section: Introductionmentioning
confidence: 99%
“…The higher number of colonies on the DBA-precoated plates than on the plates precoated with the ECM components (Fig. 3) suggests that proper stimulation of somatic cells, including Leydig cells, Sertoli cells and endothelial cells (which are necessary for the survival and proliferation of germ cells; Aponte et al 2008), supports the colony formation of gonocytes on the DBA-precoated plates. In fact, the colony formation of bovine gonocytes can be supported on GN-coated plates for the first week of culture (Fujihara et al 2011).…”
Section: Discussionmentioning
confidence: 93%
“…The colony formation of testicular cells in culture depends on the presence of germ cell populations (Aponte et al 2008), and these cell populations were strongly associated with the expression of NANOG and POU5F1 (Fig. 5b).…”
Section: Discussionmentioning
confidence: 98%